Financial Management Behavior : Case of Athletes in Indonesia - Bayu Seno Pitoyo; Muhammad Richo Rianto; Supriyanto (East Asian Journal of Multidisciplinary Research, 2022)
This study is to determine the factors that influence the financial management of weightlifting athletes in Indonesia. In this study uses quantitative research methods in which weightlifting athletes in Indonesia are the object. This study using a non-probability sampling technique and using a sample of 80 respondents. The design used in this study is hypothesis testing using a structural equitation model (SEM) – SmartPLS 4.0. The results of this study indicate that the three X variables consisting of Income, Financial Literacy, and Lifestyle have an influence on Financial Management in weightlifting athletes in Indonesia. This study has limited research objectives that only use 80 weightlifters in Indonesia as research respondents. This is used as a suggestion for future researchers. The novelty of this study combines the variables of Income, Financial Literacy, and Lifestyle on Financial Management in weightlifting athletes in Indonesia.